PEMANFAATAN SLUDGE INDUSTRI SEBAGAI ALTERNATIF MEDIA TANAM JARAK PAGAR (JATROPHA CURCAS L.) YANG BERASOSIASI DENGAN MIKORIZA ARBUSKULA - tutik nurhidayati (Purifikasi, 2007)
The aim of this research is to decrease the heavy metal contents and to improve the industrial sludge quality by applying arbuscula mycorhiza, so that it may be used as plant growth alternative medium. The results of the study showed that (1) content of the heavy metals in the plant growth media made from mixtures of sludge and soil after treatment with Jatropha curcas L was decreased (2) the growth of J. curcas L, as showed by height, leaf width and biomass dry weight showed decreasing or inhibiting effect with the higher proportion of sludge than that of the soil, where mycorhiza was not inoculated. In contrast, the smaller sludge proportion to soil, where mycorhiza was inoculated, the higher the plant growth rates.